Gestión pública y su incidencia en el desarrollo comunitario de los beneficiarios de la fundación vivir para servir del cantón valencia año 2023. - Pacheco Ayala, Tatiana Valeria (2025)
The following research study was conducted in Valencia canton, Los Ríos province, Ecuador, during the year 2023, focusing on the beneficiaries of the Vivir para Servir Foundation, a population of 275 people. The main objective was to analyze how public management affects the community development of this population, using surveys and interviews as key tools for data collection. The initial analysis revealed significant deficiencies in public management, including the lack of monitoring and evaluation of community projects, inadequate allocation of financial and technical resources, and limited community participation in decision-making processes. These issues create a disconnect between the actual needs of the community and the actions implemented by public institutions. Through an 11-question survey directed at a representative sample, perceptions of the effectiveness of public management, accessibility to basic services, sustainability of projects, and equity in resource distribution were evaluated. Interviews conducted with the foundation’s authorities complemented this information, identifying challenges and opportunities to improve collaboration between public management and local development initiatives. As a result, a community development plan was designed to enhance the impact of interventions through strategic planning, active community participation, and constant evaluation of results in terms of social, economic, and community well-being. This plan is presented as a key tool to promote sustainable development in Valencia canton.